Fenomena Doom Spending: Analisis Komunikasi Digital terhadap Perilaku Konsumtif Generasi Z di Tiktok - Dwi Asyila Sabrina Br. Saragih; Tengku Walisyah (Aksioreligia, 2026)
The rise of doom spending among Generation Z on the TikTok platform reflects a financial literacy crisis as well as vulnerability to manipulative digital marketing strategies. This study aims to analyze the digital communication patterns on TikTok that trigger doom spending behavior, identify usage motives and consumptive effects based on the uses and effects theory, and formulate mitigation recommendations. Utilizing a qualitative content analysis approach based on Krippendorff’s framework, data were collected through visual documentation consisting of screenshots of user comments, product reviews, and live shopping interactions on the @dictionarei and @lozyhijab_ accounts. Grounded in Uses and Effects Theory, the findings identify four primary digital communication mechanisms driving impulsive buying: FOMO engineering, social proof amplification, parasocial relationship exploitation, and frictionless commerce integration. The results indicate that usage motives—such as entertainment, information seeking, social affiliation, and identity expression—produce mutually reinforcing cognitive, affective, and conative effects that actively construct artificial needs. This phenomenon is criticized as modern extravagance (tabdzir and israf) that contradicts the principles of qana'ah and hifz al-mal. This study recommends strengthening social commerce regulations, enhancing digital and financial literacy among Gen Z, and internalizing self-control values to foster more responsible digital consumption.